Incidencia en el transcurso natural de la escorrentía en la parroquia urbana La Providencia en el cantón Machala - Ordóñez Yagual, Dennis Stalin (2017)
In recent years in the countries of the world urbanization processes are increasing, demanding a high level of movement of people to the cities, this process directly influences the hydrological cycle and in most cases in a negative way , Which leads to a considerable reduction of infiltration increasing surface runoff by creating surfaces with little waterproofing such as paving and buildings that do not allow filtration to the ground whereby the water is forced directly into drafts or currents in some Cases presenting problems of floods or floods. What happens when a basin is urbanized? A large part of its surface that had vegetation or natural soil becomes impermeable, due to the construction of houses (roofs and patios), streets, sidewalks and parking lots. The effects of this waterproofing are several, for example the rain no longer infiltrates and therefore the volume of runoff increases, its surface is smoother, so that it transports more efficiently the flow and there is less storage. Proposals for already consolidated urban areas focus on the restoration of urban hydrological conditions in river basins and the control of stormwater runoff pollution. The restoration of the hydrological conditions of the consolidated urban watersheds are determinant for the reduction of the volume of runoff and peak flows. In the present work the hydrological need is presented to the incidence of the urbanization in the natural course of the runoff. The objective was to develop a methodology for the incidence of urbanization in the natural course of the runoff through the application of geographic information systems to identify those sections of urban streets susceptible to flooding in the urban parish of La Providencia in Canton Machala. For the elaboration of the methodology by means of a computerized mathematical model the spatial and temporal behavior of the precipitation by design rain was established to obtain the digital model of elevation with the urban infrastructure of the zone to delimit the sub-basins and micro-basins to determine the streets Urban areas susceptible to flooding. To obtain the design rainfall by applying a hydrological model, which will be described later in the work, it will be defined for return periods of 2, 5, 10, 20, 50, 100 and 200 years. For the physical model it is elaborated by GIS software, it is determined the planimetry of the zone, the topographical relief and the uses of soil and with last, with base the configuration the physical model, the sub-basins and micro-basins are determined; Based on what is done, determine the tie rods and speed at street level that will define the flood risk map. Hydrological models are tools that help us to understand, explore and analyze these processes and how to evaluate sustainable management options. The calculation of values of flow or runoff from design rainfall is predicted to a series of hydrological phenomena that modify the volume of water until reaching its final condition. These processes are divided into three groups: Excess precipitation, Transformation and, Transit